2022
DOI: 10.14569/ijacsa.2022.0130233
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Mathematics Learning Application Selection using Fuzzy TOPSIS

Abstract: Impressive evolution of technology increased the usage frequency of smart mobile phones, and hence abundance in the quantity of available mobile applications has emerged as the vital problem of inventing practical and efficient ways for selecting suitable mobile applications for the desired use. Today, there are almost three million apps only at the Google Play store. Therefore, the need for an automated, effective, and less timeconsuming approach towards suitable mobile application selection to choose the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…When the market scores of these applications are examined, it is seen that they are among the top seven applications. In this context, it can be said that these findings support conclusions in the literature that market score should not be the only selection criterion in choosing an application (Dubé et al, 2020;Başaran & Homsi, 2022). Because, it has been found that the ranking made with TOPSIS based on the evaluation scores of the teachers is different from the ranking of the applications according to the market scores.…”
Section: Findings and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When the market scores of these applications are examined, it is seen that they are among the top seven applications. In this context, it can be said that these findings support conclusions in the literature that market score should not be the only selection criterion in choosing an application (Dubé et al, 2020;Başaran & Homsi, 2022). Because, it has been found that the ranking made with TOPSIS based on the evaluation scores of the teachers is different from the ranking of the applications according to the market scores.…”
Section: Findings and Discussionsupporting
confidence: 82%
“…After the determined criteria were weighted with FAHP, they were ranked with TOPSIS and it was seen that the results obtained were different from the Google Play Store user ratings. In another study, Başaran and Homsi (2022) aimed to create a guiding model for selecting the most appropriate mathematics application. For this purpose, six applications with the highest market scores were evaluated by two experts according to 40 different criteria.…”
Section: Topsis ("Technique For Order Preference By Similarity To Ide...mentioning
confidence: 99%